Children With Cerebral Palsy Show Higher Static—But Not Higher Dynamic—Motor Fatigability in Grip and Pinch Tasks Than Children With Typical Development Do. Issue 2 (11th November 2022) - Brauers, Lieke; Smeets, Rob; Feys, Peter; Gordon, Andrew M; Janssen-Potten, Yvonne; Ortibus, Els; Feys, Hilde; Rameckers, Eugene; Klingels, Katrijn
Abstract: Objective: The purpose of this study was to investigate differences in static and dynamic motor fatigability during grip and pinch tasks between children with unilateral spastic cerebral palsy (USCP) and children with typical development (TD) and between preferred and nonpreferred hands. Methods: Fifty-three children with USCP and 53 age-matched children with TD (mean = 11 years 1 month; SD = 3 years 8 months) participated in 30-second maximum exertion sustained and repeated grip and pinch tasks. For sustained tasks, the Static Fatigue Index and the ratio of mean force between the first and last thirds of the curve were calculated. For repeated tasks, the ratio of mean force and the ratio of numbers of peaks between the first and last thirds of the curve were calculated. Results: Higher Static Fatigue Index scores for grip and pinch were found with USCP in both hands and between hands in both groups. Dynamic motor fatigability showed inconsistent results, with higher levels of fatigability in children with TD than in children with USCP for grip in the ratio of mean force between the first and last thirds of the curve in nonpreferred hands and in the ratio of number of peaks between the first and last thirds of the curve in preferred hands. Conclusion: Higher motor fatigability in children with USCP than in children with TD was found for static but not dynamic grip and pinch. Underlying mechanisms may play different roles in static and dynamic motor fatigability. Impact: These results highlight that static motor fatigability in grip and pinch tasks should be part of a comprehensive upper limb assessment and that this could be the target of individualized interventions.